2016
DOI: 10.1038/srep36026
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach using C. elegans DNA damage-induced apoptosis to characterize the dynamics of uptake transporters for therapeutic drug discoveries

Abstract: Organic cation transporter (OCT) function is critical for cellular homeostasis. C. elegans lacking OCT-1 displays a shortened lifespan and increased susceptibility to oxidative stress. We show that these phenotypes can be rescued by downregulating the OCT-1 paralogue, OCT-2. Herein, we delineate a biochemical pathway in C. elegans where uptake of genotoxic chemotherapeutics such as doxorubicin and cisplatin, and subsequent DNA damage-induced apoptosis of germ cells, are dependent exclusively upon OCT-2. We cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 59 publications
1
35
1
Order By: Relevance
“…We used the gst::gfp reporter animals to monitor oxidative stress caused by toxic compounds and showed that these animals expressed a basal level of GST-4::GFP in the intestine. However, the expression level of the GST-4::GFP was greatly stimulated following RNAi downregulation of oct-1 that led to the upregulation of oct-2 [33]. Consistent with this observation, downregulation of the oct-2 transporter gene by RNAi lowered the basal levels of GST-4::GFP expression in the reporter strain [33].…”
Section: Uptake Transporters In C Eleganssupporting
confidence: 70%
See 4 more Smart Citations
“…We used the gst::gfp reporter animals to monitor oxidative stress caused by toxic compounds and showed that these animals expressed a basal level of GST-4::GFP in the intestine. However, the expression level of the GST-4::GFP was greatly stimulated following RNAi downregulation of oct-1 that led to the upregulation of oct-2 [33]. Consistent with this observation, downregulation of the oct-2 transporter gene by RNAi lowered the basal levels of GST-4::GFP expression in the reporter strain [33].…”
Section: Uptake Transporters In C Eleganssupporting
confidence: 70%
“…First, unlike the oct-1 null animals, downregulation of oct-2 did not affect the lifespan of the animals. Second, perhaps most interesting, the depletion of OCT-2 rescued the shortened lifespan of animals already deleted for the oct-1 gene [33]. This striking observation prompted the possibility that OCT-1 might influence OCT-2 function, whereby oct-1 downregulation leads to oct-2 upregulation.…”
Section: Uptake Transporters In C Elegansmentioning
confidence: 99%
See 3 more Smart Citations